2009
DOI: 10.3899/jrheum.081285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blockade of Tumor Necrosis Factor-α with Etanercept on Surgical Wound Healing in SWISS-OF1 Mice

Abstract: Surgical wounds showed a higher degree of collagenization at 20 days in etanercept-treated versus untreated mice, with no differences in the time course of wound healing. These data suggest that biological therapies to block TNF-alpha do not affect wound healing and do not need to be suspended during the perioperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…As in our study, they found that the inflammatory cell counts in the wound area were higher in the non-treated animals although this was not statistically significant. They concluded that biological therapies, that inhibit the effect of the TNF-α molecule, does not affect wound healing and does not need to be suspended preoperatively [30]. …”
Section: Discussionmentioning
confidence: 99%
“…As in our study, they found that the inflammatory cell counts in the wound area were higher in the non-treated animals although this was not statistically significant. They concluded that biological therapies, that inhibit the effect of the TNF-α molecule, does not affect wound healing and does not need to be suspended preoperatively [30]. …”
Section: Discussionmentioning
confidence: 99%
“…En effet, le TNF alpha est essentiel au bon déroulement de la cicatrisation. Dans une étude chez la souris sous ETN, Iglesias et al ont conclu à une durée de cicatrisation similaire avec ou sans anti-TNF [44]. Plusieurs études rétrospectives [11][12][13][14] ainsi que l'étude prospective de Bibbo et al [9] n'ont pas conclu à davantage de complications chez les patients sous anti-TNF.…”
Section: Discussionunclassified
“…Experimental results of TNF-a administration in murine models of wound-healing complications have not been consistent. Although TNF-a inhibition could theoretically have a negative impact on wound-healing (13), studies by our group and other authors suggest that it may improve collagenization of the wound (14), supporting its continuation during the perioperative period (Fig 3 and 4). No data are available on the effect of rituximab on surgical complications in RA patients.…”
Section: Biological Therapiesmentioning
confidence: 99%